Głos Łodzi . pismo Regionalnej Komisji Wykonawczej NSZZ "Solidarność" Ziemi Łódzkiej, no. 60, 1988 - Popiełuszko, Jerzy; Katarasiński, Jerzy; Lerski, Witold ([s.n.], 1988)
Creation and circulation: W 1989 r. published legally titled Głos Solidarności